Minimum Alveolar Concentration of Sevoflurane for Laryngeal Mask Airway Removal in Children; the Effect of Caudal Anesthesia (Annals of Medical Research, 2021)
None
Keywords: Sevoflurane, Laryngeal Mask Airway, Caudal Anesthesia